Are serial acquirers good targets for acquisition? An accounting perspective - Nnadi, Matthias; Tanna, Sailesh (Inderscience, 2016)
This study uses the positivist agency theory to examine if serial acquirers with consistently negative cumulative abnormal returns over their past acquisitions are more likely to become targets themselves. The study is based on the assumption that firms that make repeated value reducing acquisitions and depress their stock price are more attractive targets than firms that make good returns to their shareholders through acquisitions, and whose share prices increase correspondingly. Our findings show that serial acquirers that are considered bad bidders are more likely to become targets themselves compared to those that are considered good bidders. While this is the case in the USA and Europe, we find limited evidence to show that the same disciplinary tool is applicable in other parts of the world.
Keywords: disciplinary tools; bad bidders; good bidders; takeovers; serial acquirers; accounting; shareholder returns; postivist agency theory; value reducing acquisitions; stock prices; share prices